Measuring Guests' Stay Decisions at Hotel Adiwana Suweta Ubud - Gusti Ayu Winda Putri; I Made Gede Darma Susila; Ida Ayu Karina Putri (Tourism and Hospitality Insights, 2026)
Introduction: Ubud is one of the districts in Gianyar Regency, Bali Province. Tourism development in Ubud District has great potential to develop accommodation businesses such as Hotels, Villas, Resorts, and one of them is the Adiwana Suweta Hotel located on Jalan Suweta, Ubud. The large number of competitors plus there are statements that are less than satisfactory for guests where the price is too expensive and the facilities are not optimal. This can certainly have a negative impact on the Adiwana Suweta Hotel, because in the hotel business the level of guest satisfaction is very important. This study aims to determine the room price on the decision to stay, hotel facilities partially on the decision to stay, and the room price and hotel facilities influence the decision to stay. Methods: The research method used is a quantitative approach with data collection techniques using research tools in the form of questionnaires given to consumers of the Adiwana Suweta Hotel. Sampling in this study amounted to 104 respondents. Results: The results of the study show that; (1) Price simultaneously has a positive and significant influence on the decision to stay at the Adiwana Suweta Hotel; (2) Facilities simultaneously have a positive and significant influence on the decision to stay at the Adiwana Suweta Hotel; and (3) Price and facilities simultaneously have a positive and significant influence on the decision to stay at the Adiwana Suweta Hotel. Conclusion: Suggestions for further research using a qualitative approach, such as in-depth interviews regarding the reasons behind guests' decisions to stay and adding new variables will provide a more comprehensive picture.